FORGIVENESS MODEL PROFETIK DALAM BANDINGAN STRUKTURAL TEORI KONFLIK - Ali, Syamsuri (Universitas Islam Negeri Raden Intan Lampung, 2014)
THE PROPHETIC “FORGIVENESS” MODEL IN THE STRUCTURE OF CONFLICT THEORY. This article reviews the distinction of the concept of “forgiveness” in the prophetic models compared with the concept of “forgiveness” in the theory of conflict. The argument is constructed by reviewing what had been practiced by the Prophet Muhammad PBUH while in Mecca and Medina, including the text of the Qur’an and the context of the historical reality in the hadith. The study finds out significant differences between the two models, both in the structural aspects and the procedural. The differences in the structural aspects are associated with the stages (phases) and orientation, while in the procedural aspects are related to the implementation mechanism. In addition, the prophetic “forgiveness” model was implemented in a linear fashion, whereas “forgiveness” in the conflict theory model can be implemented either in a linear fashion or simultaneously. The above-mentioned distinctions indicate that the prophetic “forgiveness” model can be an alternative to the development of conflict resolution theory. Moreover, besides it can be used as a contribution to the development of the theory of conflict resolution the prophetic “forgiveness” model can also be used as a basis for strengthening the local wisdom practices in the Muslims society, including in Indonesia.